PENYELESAIAN MODEL PENYEBARAN PENYAKIT ISPA DENGAN MENGGUNAKAN METODE RUNGE KUTTA FEHLBERG DI PROVINSI SULAWESI SELATAN: Completion Of The Spread Of Ari Disease Distribution Model Using The Runge Kutta Fehlberg Method In South Sulawesi Province - Nurazizah, Nurazizah; Nurman, Try Azisah; Syata, Ilham (Yayasan Al-Amin Qalbu, 2024)
This stud discusses the analysis and simulation of acute respiratory infection (ISPA) in South Sulawesi Province by applying the RLTSM used the Fehlberg’s Runge-Kutta method. The research is an applied research type with the aim of obtaining a model of the spread of acute respiratory infection and knowing the numerical solution of the mpdel in predicting cases future acute respiratory infection. The mathematical model for acute respiratory infection is in the farm of a system of diffrential equations that includes the variables R (Susceptible), L (Exposed), T (Infected), S (Recovered), dan M (Death). The research results obtained in 2023 with h=0,01 years using the Fehlberg’s Runge-Kutta method with initial values of R0 =458.665, L0 = 165.670, T0 = 141.755, S0 = 103.217, M0 = 9 is R100 =681.560, L100 = 107.068, T0 = 141.755, S100 = 167.445, M100 = 25.248, for order 4 results and R100 =681.559, L100 = 107.070, T100 = 57.208, S100 = 167.442, M100 = 25.247, for order 5 results. The rate of the susceptible population has increased, the exposed and infected population has decreased, the recovered population has increased and then decreased, and the death population has increased and then stabilized